P117 Acute haemorrhagic oedema of infancy: an important spot diagnosis. (June 2019) - Murphy, Greg; McGrath, Thomas; Hanley, Claire; Roche, Darren; Salim, Asad; Roche, Edna
Abstract : Background: Acute haemorrhagic oedema of infancy (AHOI) or Finkelstein/Seidlmayer disease, is an uncommon leukocytoclastic small-vessel vasculitis typically occurring between the ages of 6 months and 2 years. Despite its alarming presentation, it is benign and often has a self-limiting course. Case report: A 4-year-old girl presented to the Emergency Department with a 2-day history of a diffuse spreading erythematous rash, joint pain and swelling. She was unwell for the previous 2 weeks with cough and upper respiratory tract symptoms, and was treated with a course of co-amoxiclav. Otherwise she had no relevant past medical history. There was a widespread, macular rash that spread to form large confluent areas over the face, buttocks, torso, posterior legs, and arms [PICTURED]. The lesions had an erythematous margin with a central area of clearing. Characteristically these lesions faded in places as bruises with blue discolouration, particularly in the popliteal fossa and at the ankle, concerning for vasculitis. There was pain and swelling of both ankle joints rendering her unable to mobilise. There was a history of Sjogren's disease in the maternal grandmother. Investigations revealed an elevated white cell count of 20.5, predominantly neutrophilic, and a C-Reactive Protein of 51. Urinalysis and blood pressure were normal. Initial treatment with prednisolone and antihistamines in ED had minimal effect. Following medical and dermatology consultation, a diagnosis of Acute Haemorrhagic Oedema of Infancy was considered. She improved significantly over the next 48 hours without further intervention and was discharged home. There was complete resolution of her symptoms on follow up 2 days later. Discussion: AHOI is a rare, benign form of vasculitis. It typically follows a recent respiratory prodrome. There are overlapping features with Hennoch-Scönlein purpura (HSP) that have been described. Some have contemplated whether AHOI is merely a milder variant of HSP or a separate entity. Nevertheless, its dramatic presentation often results in consideration of more sinister ailments. Skin biopsy can confirm AHOI but if identified early, the diagnosis can be made on clinical findings alone. Conservative management is the most commonly followed approach. Renal involvement and gastrointestinal bleeding are uncommon complications. Prompt recognition of this condition can spare children from invasive investigations and unnecessary treatment, therefore heightened physician awareness of this phenomenon is paramount.